Examination of worker‐location measurement methods as a research tool for automated labor control - Navon, Ronie; Goldschmidt, Eytan (Journal of Civil Engineering and Management, 2010)
Automatic labor performance measurement is a challenging area of research. Little work has been done in this area due to its complexity and the absence of adequate research tools. The authors used the approach of indirect parameters to automate the performance measurement. In this approach, the location of the worker is measured as a function of time and special algorithms convert these data into labor inputs, or productivity. Research in this area requires a reliable method, or tool, for workers location measurement ‐ such a tool does not exist. Three methods of location measurement are examined in this paper as research tools for automated labor control: (1) manual simulation of location measurement, (2) GPS, and (3) video photography. The first two methods were found to be subjective, inaccurate and unreliable. The third was found to be suitable for the purpose of the present research. This method uses a classical time‐lapse technique, together with a video‐based method developed in the present research.First Published Online: 24 Jun 2011